A Prospective Cohort Study on Accuracy of Dorsal Tangential Views to Avoid Screw Penetration With Volar Plating of Distal Radius Fractures. Issue 9 (September 2020) - Bergsma, Minke; Bulstra, Anne Eva; Morris, David; Janssen, Michiel; Jaarsma, Ruurd; Doornberg, Job
Abstract : Objective: To assess diagnostic performance of dorsal tangential views (DTVs) to detect dorsal screw protrusion in clinical practice. Design: Prospective cohort study. Setting: Level-1 trauma center. Patients: Fifty consecutive patients undergoing volar plating for 50 distal radius fractures were prospectively included. Intervention: Fluoroscopic DTVs were routinely obtained, and screw revision was documented. Multiplanar reconstructions of postoperative CTs allowed for detection and quantification of dorsal screw penetration using reproducible measuring techniques. Main Outcome Measurements: Diagnostic performance (sensitivity, negative predictive value, positive predictive value, and accuracy) of DTV. Results: Intraoperatively, in 16 of 50 patients (32%), screws were revised based on DTV, with 13 of 218 screws (6.0%) being revised due to dorsal prominence. One screw was changed because DTV showed it was in the distal radioulnar joint. Postoperatively, in 10 patients (20%), the computed tomography revealed 12 additional screws penetrating ≥1 mm with an average of 1.8 mm (range 1.0–4.5 mm). DTV had a sensitivity of 52%, a negative predictive value of 95%, and accuracy of 95%. No ≥1-mm protruding screw remained in the third compartment. Conclusions: In one-third of our patients, the incidence of protruding screws that can cause iatrogenic extensor tendon rupture was reduced by obtaining additional DTVs. Although DTV reduces the incidence of dorsal screw penetration considerably, this study reveals limited sensitivity. Therefore, one should keep in mind that dorsal screw penetration may go unnoticed on DTVs, and proper surgical technique remains paramount of DTV. Level of Evidence: Diagnostic Level II. See Instructions for Authors for a complete description of levels of evidence. Abstract : Supplemental Digital Content is Available in the Text.